ЕКОНОМСКИТЕ ФАКТОРИ КАКО ПРЕДУСЛОВ ЗА ПОЈАВА НА КОНФЛИКТИ - Срѓан МИЛАШИНОВИЌ; Оливер БАКРЕСКИ (Bezbednosni Dijalozi, 2011)
The theoretic elaboration in this paper focuses on the economic factors as a precondition for emergence of conflicts. The increased interest for examination of this subject appeared after the end of the World War II, when many countries formed specialized scientifical andresearch institutions for researches in this domain. So, the increased interest provoced a continuous research of the economic factors, which is the fundamental presumption when seeking forms and solutions in the concept of peace building. Over-coming certain disproportions that are a result of some specifics, and ofcourse are a result of the inconsistent cumulated knowledge and the hard attitude for the reasons of conflict emergence, should give the answer for the crucial issues tied with the conflicts itself.